EVACUATION OF THE POPULATION IN EMERGENCY SITUATIONS - Rajabboev B.E. (Bright Mind Publishing, 2025)
The evacuation of the population in emergency situations is a crucial aspect of disaster risk reduction and public safety management. It entails the organized relocation of individuals from areas exposed to imminent or ongoing threats to safer locations. In the context of Uzbekistan, a country located in a seismically active region and facing risks from floods, industrial incidents, and extreme weather, the development and execution of effective evacuation plans are of particular importance. This paper examines the theoretical basis, institutional framework, and practical aspects of evacuation procedures, highlighting the roles of government agencies, emergency services, and community participation. It also addresses the challenges and opportunities in improving evacuation preparedness through education, technology, and international cooperation. The study aims to support students specializing in emergency response with a deeper understanding of evacuation strategies adapted to Uzbekistan’s specific conditions.
Keywords: Evacuation, emergency situations, public safety, disaster risk reduction, Uzbekistan, crisis management, emergency preparedness.